The mathematical critical thinking ability of Mts Students reviewed from habits of mind - Faruliansyah, Yusdi; Agus Firmansah; Putri Mubarika, Melinda; Pitasari, Kiki (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
Critical thinking is a process that involves thoroughly evaluating information to make sound decisions. This skill enables students to systematically analyze problems, address challenges in an organized manner, formulate issues, and develop effective solutions. According to PISA results, the average mathematics score of Indonesian students remains below the international average. One significant aspect of mathematics learning, particularly in the affective domain, is the habit of mind, which supports the achievement of education goals. This study aims to assess students’ critical thinking skills and describe the critical thinking processes of Islamic junior high school students in solving mathematical problems in relation to their habits of mind. A descriptive qualitative approach was employed. The subjects consisted of 48 eighth-grade students from an Islamic junior high school in Bandung, with the topic of relations and functions. Data were collected through critical thinking tests, habits of mind questionnaires, and interviews. The data were analyzed inductively to gain an in-depth understanding of students' critical thinking processes. The results showed that the average score of students’ critical thinking ability was 66%, which falls into the moderate category. Moreover, the critical thinking process in solving mathematical problems varied based on students' levels of habits of mind. Students with high levels of habits of mind. Students with high levels tended to demonstrate stronger critical thinking skills.